Genomic analysis of bacteria in the Acute Oak Decline pathobiome. Issue 1 (8th January 2019) - Doonan, James; Denman, Sandra; Pachebat, Justin A.; McDonald, James E.
Abstract : The UK's native oak is under serious threat from Acute Oak Decline (AOD). Stem tissue necrosis is a primary symptom of AOD and several bacteria are associated with necrotic lesions. Two members of the lesion pathobiome, Brenneria goodwinii and Gibbsiella quercinecans, have been identified as causative agents of tissue necrosis. However, additional bacteria including Lonsdalea britannica and Rahnella species have been detected in the lesion microbiome, but their role in tissue degradation is unclear. Consequently, information on potential genome-encoded mechanisms for tissue necrosis is critical to understand the role and mechanisms used by bacterial members of the lesion pathobiome in the aetiology of AOD. Here, the whole genomes of bacteria isolated from AOD-affected trees were sequenced, annotated and compared against canonical bacterial phytopathogens and non-pathogenic symbionts. Using orthologous gene inference methods, shared virulence genes that retain the same function were identified. Furthermore, functional annotation of phytopathogenic virulence genes demonstrated that all studied members of the AOD lesion microbiota possessed genes associated with phytopathogens. However, the genome of B. goodwinii was the most characteristic of a necrogenic phytopathogen, corroborating previous pathological and metatranscriptomic studies that implicate it as the key causal agent of AOD lesions. Furthermore, we investigated the genome sequences of other AOD lesion microbiota to understand the potential ability of microbes to cause disease or contribute to pathogenic potential of organisms isolated from this complex pathobiome. The role of these members remains uncertain but some such as G. quercinecans may contribute to tissue necrosis through the release of necrotizing enzymes and may help more dangerous pathogens activate and realize their pathogenic potential or they may contribute as secondary/opportunistic pathogens with the potential to act as accessory species for B. goodwinii . We demonstrate that in combination with ecological data, whole genome sequencing provides key insights into the pathogenic potential of bacterial species whether they be phytopathogens, part-contributors or stimulators of the pathobiome.